Exploring Narcopolis as a Postmodern Narrative and Semiotic Text - Punyashree Panda; Sayani Konar (Nalans)
Jeet Thayil’s Narcopolis (2012), inspired by his own experience as an opium and later heroin addict, paints a vivid picture of the seedy underbelly of 1970s Bombay. The novel features a multitude of characters from the opium dens of Bombay and threads multiple narratives, subversive and carnivalesque, to create a postmodern chronicle of the city. This article analyzes the narrative techniques in Jeet Thayil's novel Narcopolis (2012) to explore traits of postmodernity. It contends that the occurrence of multiple narratives, whose reliability is questionable, indicates a Barthian death of the author, encouraging the readers to give meaning to the text. Also, an inquiry into the novel’s commentary on its own narrative style indicates self-reflexivity. A study of the chronotope will be undertaken to decipher the temporality in the novel. Besides, the article will look out for possibilities of embedded narratives, plot digressions, and intertextuality. It also intends to scrutinize the novel using the tools of social semiotics. Linguistic analysis of discourse entails a monolithic approach, wherein it considers language as the only mode of interpretation of a text. Gunther Kress and Theo Van Leeuwen suggest that this limitation can be overcome by social semiotics, which studies a text in its multimodality. Signs, linguistic as well as nonlinguistic, are apparent through multiple modes, such as language, sound, visual, and so forth. The incorporation of certain pictures, changes in typography of certain pages as well as the book cover of Narcopolis poses a rich possibility of the semiotic understanding of the text through visual mode. Lastly, this article will aim to establish a connection between the narrative techniques and the semiotic interpretation of the text.